PEMANFAATAN PERPUSTAKAAN RAUSYANFIKR DALAM MENDUKUNG PROGRAM MASYARAKAT EPISTEMOLOG ISLAM (MEI) DI PONDOK PESANTREN MURTADHA MUTHAHHARI YOGYAKARTA” - Musakal, Musakal; Nurarifah, Lely; Rosdiana, Rosdiana (Gemi: Jurnal Penelitian dan Pengabdian, 2023)
Libraries have played an important role in providing a place to experience and increase interest in reading. With a high interest in reading, a person can be assured of having extensive experience, knowledge and insight which can automatically improve the quality and dignity of his life. The type of research in this article is qualitative research where the data comes directly from the first source and has not undergone processing, which is then known as primary data. This research involves 3 (three) data collection methods, including: observation method, sample method and interview method. This research uses data analysis which includes three main components, namely; Data Reduction, Data Presentation, Conclusion Drawing. The results of this research explain that the Rausyanfikr library is one of the libraries that supports the implementation of religious activities by bringing the basics of philosophical and moral thinking closer together. To realize this vision, the Rausyanfikr library is a supplier of various references needed in the dissection of the Yogyakarta Islamic Epistemology Society program. The references in question include, among others). Al-hikmah Journal 1 volume. 2) Mulla Sadra journal 5 volumes. 3) Al-Huda journal: 2 volumes and several core books for systematic in-depth discussion of philosophy.